A comparison of EGF and MAb 528 labeled with 111In for imaging human breast cancer. - Reilly, R; Kiarash, R; Sandhu, J; Lee, Y; Cameron, R; Hendler, A; Vallis, K; Gariépy, J (2000)
Our objective was to compare 111In-labeled human epidermal growth factor (hEGF), a 53-amino acid peptide with anti-epidermal growth factor receptor (EGFR) monoclonal antibody (MAb) 528 (IgG2a) for imaging EGFR-positive breast cancer. METHODS: hEGF and MAb 528 were derivatized with diethylenetriamine pentaacetic acid (DTPA) and labeled with 111In acetate. Receptor binding assays were conducted in vitro against MDA-MB-468 human breast cancer cells. Biodistribution and tumor imaging studies were conducted after intravenous injection of the radiopharmaceuticals in athymic mice bearing subcutaneous MCF-7, MDA-MB-231, or MDA-MB-468 human breast cancer xenografts or in severe combined immunodeficiency mice implanted with a breast cancer metastasis (JW-97 cells). MCF-7, MDA-MB-231, JW-97, and MDA-MB-468 cells expressed 1.5 x 10(4), 1.3 x 10(5), 2.7 x 10(5), and 1.3 x 106 EGFR/cell, respectively in vitro. RESULTS: 111In-DTPA-hEGF and 111In-DTPA-MAb 528 bound with high affinity to MDA-MB-468 cells (Ka of 7.5 x 10(8) and 1.2 x 10(8) L/mol, respectively). 111In-DTPA-hEGF was eliminated rapidly from the blood with < 0.2% injected dose/g (%ID/g) circulating at 72 h after injection, whereas 111In-DTPA-MAb 528 was cleared more slowly (3%ID/g in the blood at 72 h). Maximum localization of 111In-DTPA-hEGF in MDA-MB-468 tumors (2.2 %ID/g) was 10-fold lower than with 111In-DTPA-MAb 528 (21.6 %ID/g). There was high uptake in the liver and kidneys for both radiopharmaceuticals. Tumor-to-blood ratios were greater for 111In-labeled hEGF than for MAb 528 (12:1 versus 6:1), but all other tumor-to-normal tissue ratios were higher for MAb 528. MDA-MB-468 and JW-97 tumors were imaged successfully with both radiopharmaceuticals, but tumors were more easily visualized using 111In-labeled MAb 528. There was no direct quantitative relationship between EGFR expression on breast cancer cell lines in vitro, and tumor uptake of the radiopharmaceuticals in vivo, but control studies showed that tumor uptake was receptor mediated. CONCLUSION: Our results suggest that the tumor uptake in vivo of receptor-binding radiopharmaceuticals is controlled to a greater extent by their elimination rate from the blood than by the level of receptor expression on the cancer cells. Radiolabeled anti-EGFR MAbs would be more effective for tumor imaging in cancer patients than peptide-based radiopharmaceuticals such as hEGF, because they exhibit higher tumor uptake at only moderately lower tumor-to-blood ratios.